The Use of Mobile Journalism by Field Reporters and the Achieved Satisfactions: An Applied Study on Field Reporters in Jordanian Television Channels - ALbrezat, Mohammad Omar Hamad; Oreqat, Ahmad Ali (Dirasat: Human and Social Sciences, 2025)
Objective: The study aimed to identify the degree of field correspondents' use of mobile journalism and the achieved gratifications. It also aimed to apply the matter in question to field correspondents on TV channels in Jordan. Method: The study adopted the quantitative survey method, as it was applied to an available sample of (83) individual correspondents working for Jordanian news channels. The questionnaire was distributed as a tool for collecting information, and the study based its theoretical framework on the theory of uses and gratifications. Results: The study results showed that the technical satisfactions resulting from the use of mobile phones by field correspondents were high, with an arithmetic mean of (2.35), and professional satisfactions were moderately satisfied, with an arithmetic mean of (2.31), and the total degree of use was the mobile field correspondents are average, with an arithmetic average of (2.26), and the field correspondents were able to develop their skills in direct dialogue management through voice recording using a smart phone. Conclusions: The study recommended organizing training courses to enhance field reporters' use of mobile journalism, encourage innovation, and provide technical and professional support to field reporters.